Politiques de lutte contre les inégalités dans l'enseignement supérieur au Mexique, 2000-2018 : de l'équité territoriale à l'inclusion - Sylvie Didou Aupetit (Les éditions de la Maison des sciences de l'Homme, 2021)
We present the different stages, in Mexico, of the policies against inequality in Higher Education, with a focus on public higher education sector. We analyze changes from a territorial public strategy, directed at the growth of enrollment and system, to institutional policies for the improvement of inclusion measures aimed to discriminated groups. We take into account first the adaptive reforms of public action to those different purposes and, after, the surge of programs focused on individuals to alle-viate multiple segregations: residential, demographic, personal or ethnic. We study, secondly, the transition from a policy aimed to a large group (poor people) to one oriented to provide attention to small, but representative, diverse groups with different needs (indigenous or afro descendants students or disabled youths).